EFFECT OF CALCIUM AND COLE VIT D3 IN OVO INJECTION ON HATCHABILITY, BONE AND BLOOD BIOCHEMICAL DEVELOPMENT AT POSTHATCH - & et al., Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study to investigate the role of in ovo injection in broiler breeder (Ross-308) fertile eggs with calcium, vitamin D3 and their mixture at 18 d of incubation on hatchability, tibia bone and blood properties post-hatching, included five groups: (non-injected and in ovo injected 100 μL sterilized distill water) controls as well as eggs that were injected with the 100 μL sterilized distill water either 0.8 mg calcium (Ca), 0.8 mg Cole vit D3 [colecalciferol or 25-OHD3] and mix of 0.8 mg Ca + 0.8 mg Cole vit D3. The results showed that an in ovo injection with calcium, Cole vit D3 and their mix presented significantly higher in hatchability (%), body performances, tibia bone properties [length, breaking strength, Ca and P concentrations, ash %] and blood biochemical analysis [Ca and P minerals concentrations, vit D3 and parathyroid hormone (PTH)] at 0 and 35 d posthatch. While, blood calcitonin hormone (CT) at 0 and 35 d posthatch and blood Ca: P ratio had recorded lower concentration at 0 posthatch, however had seen non-significant differences among all the groups in tibia width and Ca:P ratio in tibia bone at 0 and 35 d posthatch and also non-significant among all the groups of in ovo injection and control in blood Ca: P ratio at 35 d posthatch. The in ovo injection with Cole vit D3 and mixture of Ca and Cole vit D3 showed more effectiveness in most characteristics.